Metastatic seminoma in a non-cryptorchid dog previously submitted to vasectomy: case report (Research, Society and Development, 2022)
The objective of this study was to describe the case of a three-year-old dog of the Shih-tzu breed, whole and not cryptorchid, treated at the Veterinary Hospital of the Centro Universitário INTA-UNINTA in the city of Sobral - CE, with a complaint of increased volume in the scrotal region. Upon physical examination, it was verified that both testes were present in the scrotum, with bilateral increase in volume, noting a firm and adherent mass in the incision region for a vasectomy procedure performed six months ago in another veterinary establishment. The animal was referred for surgical treatment with orchiectomy, scrotal ablation and subsequent exploratory laparotomy, in view of the findings at the time of orchiectomy and abdominal ultrasound indications. The macroscopic and microscopic analyzes of the testes and the entire extension of the affected omentum, observed during the operation, led to the diagnosis of seminoma with metastasis to the omentum. In view of the above, the importance of the description of this case brings veterinary clinical relevance that can facilitate research and new reports with the same content addressed, associated with the scarcity of works that can relate the performance of vasectomy with the boost in the development and dissemination of testicular neoplasms, as well as adds epidemiological data to seminomas in dogs, taking into account that early assessment of the male reproductive system can influence the achievement of better prognostic results for patients, providing more information to the study of testicular neoplasms.